The Socialist Economics of Karl Marx and His Followers - Veblen, Thorstein (Quarterly Journal of Economics, 1907)
Journal Article The Socialist Economics of Karl Marx and his Followers Get access Thorstein Veblen Thorstein Veblen Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 2, February 1907, Pages 299–322, https://doi.org/10.2307/1883435 Published: 01 February 1907